Wet-mix spray: improvement on its mix proportion using GGBS / Mohamad Ariffin Abdul Basar - Abdul Basar, Mohamad Ariffin (1997)
Shotcrete is an excellent placement method for repair of vertical and overhead surfaces. It is particulariy cost effective for repair of large, shallow areas or where farmwork is impractical. Shotcrete also forms an excellent bond to the substrate, usually superior to the bond achieved with cast in situ concrete. Ten ( 10 ) years ago, shotcrete admixtures were scarce. Many successful repairs have been, and still are, performed with shotcrete containing only sand, cement and water. This project is to analyse the mix proportion and repair material used in concrete repair works. The method of interest is by wet-mix spray. GGBS as a partial replacement material to OPC is used and superiasticiser, bonding agent and accelerator are the ingredients utilized to make the concrete durable. The experimental program comprises of 6 levels of GG8S replacement to OPC namely 0, 30, 40, 50%, 60%, and 70%. The strength development test is carried out on 100mm cube at 1,3, 7, 14, and 28 days and water curing is adopted.